Sistem Penjualan Makanan Ringan Dengan Menggunakan Metode Analsis SWOT - Zurea Nur Meyati (UNIVERSITAS PELITA HARAPAN, 2021)
Abstract– There are so many snacks lovers in Indonesia, snack lovers not only come from one group but also from various circles of society. Types of snack businesses that are in great demand by various groups are toast, various noodles, French fries, fried bananas and pancakes. In some places this snack food business is still experiencing problems related to the sales process, where the menu paper is often torn and wet, causing errors in ordering. These problems resulted in losses in terms of finance, time and energy. This snack sales system can help overcome these problems with the aim of increasing sales volume and the accuracy of order data. Seeing the situation and conditions in this business, a business process analysis and system analysis are carried out using the SWOT analysis method.Keywords: Sales, Snacks, SWOT